Comparative Quantitative Analysis of Leading Business Intelligence Software Platforms (Texas Journal of Multidisciplinary Studies, 2022)
In this study, the Business Intelligence (BI) problem domain is considered. A generalized stack of BI software architecture is reviewed, core techniques and capabilities of Business Intelligence are outlined. Among leading BI platforms were considered Power BI, QlikView, and Tableau, which were compared from the viewpoint of their BI capabilities. Different similarity measures were used to compare BI platforms and evaluate their rating based on user feedback.